(untitled) (Bangladesh Medical Journal Khulna, 2014)
Teaching and learning is a lifelong process for human being. It ends with the end of lives. The professional teachers of all subjects are doing very tuff job. The adult learner only learns if they like the lecture or speech. So, the lecture should be made interesting or attractive. The teacher has to be skilled in teaching and lecturing methods. For quality and effective lecturing all teachers should know the modern techniques of teaching. Therefore training of all teachers is a must. All academic institutions need to arrange training for their teachers. The present article suggests some important tips for developing lecture and teaching skills for effective and quality teaching which might be helpful to those teachers who are not getting institutional training. One or more of the tips mentioned in this article may be used according to the topics during lecture time. DOI: http://dx.doi.org/10.3329/bmjk.v46i1-2.18236 Bang Med J (Khulna) 2013; 46 : 24-27